ROS anchor PAMPs-mediated extracellular HMGB1 self-association and its dimerization enhances pro-inflammatory signaling - Man Sup Kwak; Myeonggil Han; Yong Joon Lee; Seoyeon Choi; Jeonghwa Kim; In Ho Park; Jeon-Soo Shin (Redox Biology)
Many cellular proteins form homo- or hetero-oligomeric complexes through dimerization, and ligand oligomerization is crucial for inducing receptor oligomerization. Intermolecular disulfide bond formation is critical for protein oligomerization that regulates biological functions. HMGB1 is a nuclear protein that acts as a DAMP when secreted. HMGB1 is redox-sensitive, contains three cysteines: Cys23, Cys45, and Cys106, and its function varies depending on the redox state of the extracellular space. However, the homo-dimerization of extracellular HMGB1 and its immunological significance have not been identified. In this study, we investigated the immunological significance of Cys106-mediated HMGB1 homo-dimerization. In the extracellular environment, LPS and LTA induced HMGB1 self-association leading to H2O2 anchoring Cys106–Cys106-mediated HMGB1 intermolecular disulfide bond formation. Despite treatment with H2O2, LPS, or LTA, HMGB1 dimerization was blocked in presence of Cys106 residue mutation, the ROS scavenger NAC, and the thiol-reducing agent DTT. Inflammatory stimulation induced the secretion of monomeric HMGB1 but not dimeric HMGB1. HMGB1 dimerization was promoted by PAMPs and H2O2 in the extracellular environment. Compared to monomeric HMGB1, Cys106–Cys106-linked dimeric HMGB1 significantly enhanced intracellular NF-κB signaling and cytokine production through increased direct binding affinity for TLR2 and TLR4 and effective HMGB1-mediated delivery of PAMPs to their receptors. Therefore, we have demonstrated that dimeric HMGB1 enhances its effect on pro-inflammatory signaling.